Co-teaching within diversity: A disruptive productive source of professional development - Jeannin, L.; Sing, N. (South African Journal of Higher Education, 2018)
This self-reflective study explores how culturally diverse faculty members can benefit from co-teaching in higher education classes. It reflects on a teaching collaboration between two researchers-practitioners from different cultural and academic backgrounds in a South African university. The co-teachers shared equal responsibility for a one-month research seminar. The leading argument of this paper is that co-teaching within diversity is a key driver for disruptive and productive professional development, as co-teaching exposes faculty members to pedagogical activities and discourses they would not otherwise have experienced. It enables them to move beyond their comfort zone, take risks collectively, and learn reciprocally. The qualitative findings are organised in a model that conceptualises the co-teaching process, unpacking the relationship between empowering trust, emerging complementarities, reciprocal learning, and professional identity affirmation. The model can help teachers reap the benefits of co-teaching in culturally diverse environments.